Kidney function after liver transplantation: the contrasting roles of inflammation and tubular repair - Goerlich, Nina; Kim-Schulze, Seunghee; Kotanko, Peter; Grobe, Nadja; Wang, Xiaoling; Samans, Bjoern; Douglas, Joe; Enghard, Philipp; Molinari, Paolo; Fribourg, Miguel; Cravedi, Paolo; Levitsky, Josh (Frontiers in Transplantation, 2024)
Kidney injury is a significant complication in end-stage liver disease (ESLD), leading to increased morbidity and mortality. While liver transplant alone (LTA) can promote kidney recovery (KR), non-recovery associates with adverse outcomes, but the underlying pathophysiology is still unclear. We studied 10 LTA recipients with or without kidney failure (KF) and measured serum levels of OPN and TIMP-1 (previously identified predictors of KR), 92 proinflammatory proteins (Olink), and urinary cell populations. Our findings revealed elevated OPN and TIMP-1 levels in KF patients, strongly correlated with tubular epithelial cells in urine. Proteomic analysis showed distinct profiles in KF, non-KF, and healthy donors, indicating an ongoing proinflammatory signature in KF. Cytokines correlated with OPN and TIMP-1 levels. We propose that high pre-LTA OPN and TIMP-1 levels are crucial for tubular regeneration and normalize with kidney recovery. Insufficient pre-LTA OPN levels may lead to persistent kidney failure. Our present data also newly indicate that kidney failure post-LTA is an active condition, in which tubular cells are persistently shed in the urine. The strict association between systemic inflammation and tubular cell loss suggests a pathogenic link that could offer therapeutic opportunities to promote kidney recovery.